INVESTMENT POLICY IN «GREEN ENERGY» IN UKRAINE DURING THE MARITAL STATE - MATIICHUK, Liubomur; NOVOSAD, Oksana; SHABALA, Oleksandr; PAVLOVA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Unfortunately, our country is at the center of the third crisis, which is related to the energy complex. Due to the constant shelling of energy infrastructure facilities, Russia, the aggressor country, is depriving it of the opportunity to use energy carriers normally and efficiently and to provide light to some territories of our state fully. Even though the countries of the European Union are moving in the direction of a complete refusal to import crude oil from the aggressor country Russia, unfortunately, such steps together with the sanction packages do not stop the latter, and the Russian Federation continues to commit atrocities on the territory of our state. Despite everything, the joint work of energy workers makes it possible to get rid of problems with power outages promptly, and if not entirely, then to significantly solve the issue of electricity supply. The stocks of the countries of Europe today are approximately 92% for the current winter period, but the negative dynamics regarding the deficit for 2023 are still taking place. It is not a secret for anyone that today, our planet’s resources are running out. If not today, then tomorrow, the "raw material" given to us by the earth will run out. However, in the future, it is not only worth it but also necessary to stay on course for the development and effective functioning of alternative energy sources because this may be the only source of light and heat on our planet. Investing in and supporting greening programs, the transition to renewable energy sources in European countries and beyond is developing relatively rapidly today. It is clear that in order to inject relevant financial resources, this or that industry is obliged to provide appropriate security guarantees both at the legal level and at the level of the investment object itself, with the help of relevant legal norms, contracts, documents, etc. However, despite the global transformation, many people willing to invest have suspended the development of solar and wind projects due to the energy crisis. The result of the aforementioned negative dynamics in the direction of investing was COVID-19 and then the large-scale invasion of Ukraine by the aggressor country Russia. Thus, activity in the direction of financial investment in alternative energy sources is lower today. However, there are prospects and future in this field in our country. Prospects and development of alternative energy sources will be a massive success in the future. The discovery of new opportunities, plans, and mechanisms for the effective use and implementation of alternative energy sources will make it possible to develop "green" energy and engage in environmental protection simultaneously. The question of investments may disappear when Ukraine wins the victory over the aggressor. New opportunities and active cooperation with European partners will help restore and rebuild our state and create an appropriate investment climate for foreign partners from Europe and other friendly countries.